PERAN KOPERASI UNIT DESA HARAPAN JAYA DALAM MEMBANTU PEREKONOMIAN ANGGOTA - Fibby Krizia; Yulia Suriyanti; Munawar Thoharudin (STKIP Persada Khatulistiwa Sintang, 2022)
The role of the Village Unit Cooperative (KUD) in improving the welfare of members is not only by distributing credit assistance or loans to members with low interest but can also be in the form of assistance in buying and selling products, assistance in plant care and procurement of seeds. This study aims to narrate and describe the role of the Harapan Jaya Village Unit Cooperative in Dak Jaya Village and the factors that influence this role. Qualitative descriptive research method. Data collection techniques used in this study were interviews, observation and documentation. The results of the study concluded that the role of the Harapan Jaya Village Unit Cooperative in Dak Jaya Village in helping to improve the economy of its members was quite organized, systematized and fair which was stated in the agreement decided at the Annual Member Meeting (RAT) of the cooperative members. Technically the assistance is tailored to the needs of members, namely, marketing the harvest and providing business capital (performing assistance or training and conducting evaluations)